PERMASALAHAN HUKUM, MORAL DAN SOSIAL DALAM AKULTURASI BUDAYA EPOS RAMAYANA DI IMDONESIA. - Soelistyo Budi, Henry (Magister of Law, Faculty of Law, University of Mataram, 2024)
In line with the creative economy policy, it is advisable for Indonesians to cultivate prolific thoughts, ideas, and intellectual abilities to create various copyrighted works as mandated in Law Number 24 of 2019. In this context, one of the potential forms of creativity to be encouraged is the creation of new artistic works based on cultural acculturation. Indonesia also preserves several traditional works from foreign origins seamlessly integrated into the fabric of community traditions. Prominent instances include Valmiki’s Ramayana epic from India and the traditional Chinese Barongsai dance, both of which have acculturated with Indonesian artistic works. This socio-legal research aimed to examine the potential problems encountered in the process of cultural acculturation from the legal, moral, and socio-political aspects of relations between countries. A comprehensive method was used, including statutory, historical, and comparative analyses. The results showed that cultural acculturation was a neutral process capable of giving rise to unique, novel, and improved creations, provided the process was executed carefully in the sense of respecting cultural values, ethical considerations, and legal norms properly. In the context of the creative economy, new creations resulting from acculturation possessed high commercial value, supporting the development of the national economy.